User acceptance of SaaS-based collaboration tools: a case of Google Docs. Issue 3 (13th April 2015) - Tan, Xin; Kim, Yongbeom
Abstract : Purpose: – The purpose of this paper is to identify and understand factors that influence users' acceptance of Software-as-a-Service (SaaS) collaboration tools in organizational settings. Design/methodology/approach: – This paper develops a research model based on the Expectation Confirmation Model (ECM). Using data collected from a field study of Google Docs, the research model and related hypotheses are tested by structural equation modeling. Findings: – Users' confirmation with expectations positively affect their perceived usefulness and satisfaction level; Users' perceived usefulness and satisfaction positively affect their intention to continue using such collaboration tools. Users' prior experience with such tools and their IT skills have a moderating effect on the relationships among confirmation, perceived usefulness, satisfaction, and continuance intention. Research limitations/implications: – This study identifies the theoretical foundations of user acceptance of SaaS collaboration tools in the context of mandatory adoption. This empirical study, based on an established theoretical foundation, will help the research community to gain a deeper understanding of user acceptance of cloud computing technologies, in particular, SaaS collaboration tools. Practical implications: – The findings of this study can provide vendors and implementing organizations with useful strategies and tactics to enhance users' acceptance of SaaS collaboration tools. Originality/value: – With the increasing popularity of cloud computing technologies, there have been ongoing concerns about the effectiveness of SaaS collaboration tools in organizational settings. This study is one of the first empirical research to examine the factors influencing users' acceptance of SaaS collaboration tools.